Bacteriospermia and Male Infertility: Role of Oxidative Stress - Das, Sandipan; Roychoudhury, Shubhadeep; Dey, Anwesha; Jha, Niraj Kumar; Kumar, Dhruv; Roychoudhury, Shatabhisha; Slama, Petr; Kesari, Kavindra Kumar (Advances in experimental medicine and biology, 2022)
Male infertility is one of the major challenging and prevalent diseases having diverse etiologies of which bacteriospermia play a significant role. It has been estimated that approximately 15% of all infertility cases are due to infections caused by uropathogens and in most of the cases bacteria are involved in infection and inflammation leading to the development of bacteriospermia. In response to bacterial load, excess infiltration of leukocytes in the urogenital tract occurs and concomitantly generates oxidative stress (OS). Bacteria may induce infertility either by directly interacting with sperm or by generating reactive oxygen species (ROS) and impair sperm parameters such as motility, volume, capacitation, hyperactivation. They may also induce apoptosis leading to sperm death. Acute bacteriospermia is related with another clinical condition called leukocytospermia and both compromise male fertility potential by OS-mediated damage to sperm leading to male infertility. However, bacteriospermia as a clinical condition as well as the mechanism of action remains poorly understood, necessitating further research in order to understand the role of individual bacterial species and their impact in male infertility.
Keywords: reaktivní formy kyslíku; lidé; Infertility; Infertility, Male; Sperm parameters; Oxidative Stress; mužská infertilita; Spermatozoa; Humans; ROS; Inflammation; antioxidancia; Bacteriospermia; mužské pohlaví; spermie; oxidační stres; Leukocytes; Reactive Oxygen Species; Male; Antioxidants; Uropathogens; Infection